Involvement of p300 in caffeine-induced hyper-acetylation of histones at the MEF2 binding domain on the Glut4 gene - Chetty, Kovin Ashley (Department of Molecular and Cell Biology, 2014)
Includes abstract. Includes bibliographical references.